A New Rock Joint Generation Method and Its Verification in PFC2D - Lielie Li; Mingli Xiao; Cai Tan (Advances in Materials Science and Engineering)
The first part of this paper presents the major drawbacks of the traditional methods for generating joints in Particle Flow Code 2D (PFC2D). Violent oscillations in the postpeak shear stress and shear-induced dilation in the normal direction occur in specimens generated by directly removing bonds in joints and using the discrete fracture network (DFN) method. The specimens generated by the additional wall method can be used to simulate realistic shear mechanical properties in the direct shear test, but it is difficult to achieve a uniform initial stress distribution within the specimen due to the constraint of particle motion. The second part of this paper explores an improved method to generate realistic joints based on the particle grouping technique and the smooth joint model, and the validity of this method is verified by a set of numerical direct shear tests. The numerical results show that the proposed joint generation method can effectively eliminate the oscillation of the postpeak shear stress and shear-induced dilation in the normal direction. In addition, the mechanical behaviours of the rough jointed rock mass correspond well with the theoretical results obtained from Patton’s and Barton’s models. The proposed model can also simulate the asperity degradation of rough jointed rock masses.